Challenges and Barriers of Physical Activity Among Pediatric Patients with Type 1 Diabetes Mellitus and Their Parents: A Systematic Review - Sekar Sari; Ika Yuni Widyawati; Elida Ulfiana (Pediomaternal Nursing Journal, 2022)
Introduction: Pediatric patients with type 1 diabetes mellitus (T1DM) and their parents seems unsure about participating in physical exercise. We explored the challenges and barriers experienced by pediatric patients with T1DM and their parents in implementing physical activity. Methods: This study used a systematic review design with a literature search in CINAHL, PubMed and Scopus, from May to July 2022. The inclusion criteria used a primary study with the outcomes of research studies explaining the status and barriers to implementing physical activity, and restricted the publication year from the year of 2017-2022. The PRISMA guideline anchored in the organization of this systematic review study. Results: Seven study articles, four qualitative and three quantitative studies, were included in the final synthesis. The challenges consist of the motivation and high level of self-efficacy had been well demonstrated as significant factors in the internal group. While barriers of implementing adequate physical activity are the parent's fearness about hypoglycemia risk while being physically active, parental fears and pressures in preparing a healthful diet to keep their children active and safe, stigma, demand of supportive ambiance from the family members, school, and peers, the sufficient level of knowledge, and the limited number of technology tools provided to assist physical exercise practice were recognized as the barriers burdened the T1DM management in the external factor group. Conculusion: The most prominent challenge perceived was the fear of hypoglycemia due to the inappropriate level of physical activity.